2015
DOI: 10.1016/j.adolescence.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the associations between three types of adolescents' romantic involvement and their engagement in substance use

Abstract: Using data on 838 middle adolescents, the current study compared the associations between three types of romantic involvement and alcohol, tobacco, and marijuana use. Offtime (i.e., serious romantic relationships) but not on-time (i.e., romantic socializing and dating) types of involvement were expected to be associated with increased odds of using each substance. Participating in romantic socializing was unrelated to substance use and dating was only positively associated with alcohol use. Participation in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Further, they suggest dating may be a risk factor for marijuana use among young SGM men. This was surprising because in past research, there have generally been no gender differences (Fleming et al, 2010; Staff et al, 2010), and any evidence of romantic involvement increasing marijuana use has been limited to early and middle adolescence (Beckmeyer, 2015; Furman and Collibee, 2014). The positive association between romantic involvement and marijuana use may persist into young adulthood among male SGM partly because substance use declines less with age among SGMs than in heterosexuals (Green and Feinstein, 2012).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Further, they suggest dating may be a risk factor for marijuana use among young SGM men. This was surprising because in past research, there have generally been no gender differences (Fleming et al, 2010; Staff et al, 2010), and any evidence of romantic involvement increasing marijuana use has been limited to early and middle adolescence (Beckmeyer, 2015; Furman and Collibee, 2014). The positive association between romantic involvement and marijuana use may persist into young adulthood among male SGM partly because substance use declines less with age among SGMs than in heterosexuals (Green and Feinstein, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…Because we did not collect detailed data on partners or relationships, we could not assess whether findings were influenced by partner gender, gender composition of the relationship (same- vs. different-sex), partner’s substance use, or characteristics of the relationship (e.g., commitment, quality). Future research should also account for relationship commitment, given evidence that serious relationships, but not casual or group dating, increase adolescent substance use (Beckmeyer, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From recent research, it is becoming clear that romantic involvement and the quality of romantic relationships during middle and late adolescence help to explain variability in several psychosocial adjustment outcomes, including depressive symptoms, externalizing problems, and substance use (e.g., Beckmeyer, 2015; Collibee & Furman, 2015; Ha, Dishion, Overbeek, Burk, & Engels, 2014). Romantic experiences during early adolescence (10–14 years), however, can be difficult to study because few young adolescents are engaged in romantic relationships (Carlson & Rose, 2007; Roisman, Booth-LaForce, Cauffman, & Spieker, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, participants stated that peers were often the primary way to obtain drugs or make certain drugs with local ingredients (edible cannabis products), as reported elsewhere [ 19 ]. In addition, our participants suggested that emotional relationships between girls and boys can play a role in substance use initiation, especially for girls who receive pressure from boyfriends or as a coping mechanism during relationship disturbances [ 48 ]. In contrast, participants also believed that having close friends who make good choices and those not engaged in high-risk activities could act as a protective factor against substance use, as documented previously [ 19 , 30 , 39 ].…”
Section: Discussionmentioning
confidence: 99%